Plantago hatschbachiana (Plantaginaceae), a critically-endangered new species from sandstone grasslands in Brazil, and an updated identification key to Plantago in Brazil and Paraguay - Hassemer, Gustavo (Phytotaxa, 2016)
This article describes Plantago hatschbachiana, a narrowly-endemic new species from sandstone grasslands in Brazil. Specimens of this species were until now being identified as P. commersoniana. Plantago hatschbachiana is here assessed as critically endangered as it apparently only survives in one of its three recorded localities where it is currently threatened by an invasive shrub. In addition to that, the authorship of the name P. commersoniana is here discussed, and an updated identification key to Plantago in Brazil and Paraguay is here provided.